2006
DOI: 10.1081/dis-200066734
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence Properties of CdSe Nanocrystals from Water into Organic Phase Using 1‐Dodecylmercaptan as Phase Transfer Reagent

Abstract: Citrate-stabilized CdSe nanocrystals in an aqueous solution were transferred into various organic solvents using thiol as phase transfer reagent. Disappearance of band-edge emission from thiol-capped CdSe nanocrystals was observed in organic solvents. By UV light irradiation, the band-edge emission was activated. The aggregates of CdSe nanocrystals were observed by TEM. The mechanism of formation for the CdSe aggregates is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Purification of nanoparticles by centrifugation (purification-dissolution method) [9] is also widely used in the fabrication of nanocomposite materials, but this method is technologically complex and labor intensive [10]. Since small CdSe nanoparticles are known to be able to be quickly extracted in water-immiscible organic solvents [11], we proposed a method for the preparation of CdSe nanocrystals by electrosynthesis from aqueous solutions with their simultaneous extraction into xylene. Empirically, we have found that along with the formation of large CdSe cathode deposits (20-150 nm) a colloidal solution of CdSe nanoparticles (2-5 nm) is also formed during dc electrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Purification of nanoparticles by centrifugation (purification-dissolution method) [9] is also widely used in the fabrication of nanocomposite materials, but this method is technologically complex and labor intensive [10]. Since small CdSe nanoparticles are known to be able to be quickly extracted in water-immiscible organic solvents [11], we proposed a method for the preparation of CdSe nanocrystals by electrosynthesis from aqueous solutions with their simultaneous extraction into xylene. Empirically, we have found that along with the formation of large CdSe cathode deposits (20-150 nm) a colloidal solution of CdSe nanoparticles (2-5 nm) is also formed during dc electrolysis.…”
Section: Introductionmentioning
confidence: 99%